Deviant opera sex, power, and perversion on stage - Englund, Axel (University of California Press, 2020)
"For decades now, radical stage directors have repeatedly dressed canonical operas--from Handel and Mozart to Wagner and Puccini and beyond--in whips, chains, leather, and other regalia of SM and fetishism. Deviant Opera seeks to understanding this phenomenon, approaching the visual code of perversion as a contemporary lens through which opera focuses and scrutinizes its own configurations of sex, gender, power, and violence. The emerging image is that of an art form which habitually plays with an eroticization of cruelty and humiliation, inviting its devotees to take sensual pleasure in the suffering of others. Ultimately, this species of opera fantasizes about breaking through the boundaries of its own role playing, pushing its erotic power exchanges from the enacted to the actual"--